Preparation method and application of catalytic electrode synthesized at room temperature

By forming a corrosion-resistant and sulfur-repellent layer on a nickel foam substrate, the problem of easy corrosion of sulfide electrocatalysts in high-concentration sulfur environments is solved, realizing a low-cost and efficient sulfur oxidation reaction. It exhibits excellent catalytic activity and stability and is suitable for long-term catalytic sulfur oxidation reactions.

CN121472904APending Publication Date: 2026-02-06GUANGXI UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511379535.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

In existing technologies, sulfide electrocatalysts are easily corroded and passivated in high-concentration sulfide environments, resulting in shortened catalyst lifespan. Furthermore, the sulfur oxidation reaction consumes a lot of energy, making it difficult to achieve efficient recovery of elemental sulfur and treatment of environmental pollutants.

Method used

A catalytic electrode was prepared by impregnating a blank nickel foam substrate with an iron salt solution to form an anti-corrosion layer, and then electrodepositing a cobalt salt solution to form a sulfur-repellent layer. The substrate was a blank nickel foam substrate, the anti-corrosion layer was treated with an iron salt solution, and the sulfur-repellent layer was treated with a cobalt salt solution by electrodeposition.

Benefits of technology

A low-cost catalytic electrode was prepared under ambient temperature conditions, which prevented substrate corrosion and effectively desulfurized the product. It exhibited excellent catalytic activity and stability, and was able to achieve sulfur oxidation reaction with low overpotential at high current density, thus extending catalyst life and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121472904A_ABST
    Figure CN121472904A_ABST
Patent Text Reader

Abstract

The invention discloses a catalytic electrode which comprises a substrate, and an anti-corrosion layer and a sulfur-phobic layer which are sequentially attached to the substrate, the substrate is a blank foamed nickel substrate, the anti-corrosion layer is formed by dipping the foamed nickel substrate with a ferric salt solution, and the sulfur-phobic layer is formed by processing a precursor with a cobalt salt solution through electro-deposition. Accordingly, a corresponding preparation method is also established, a blank foamed nickel substrate is adopted, firstly, the foamed nickel substrate is subjected to dipping treatment with an iron salt solution to obtain a precursor with an anti-corrosion layer, and then the precursor is subjected to electro-deposition treatment with a cobalt salt solution to form the sulfur-phobic layer on the anti-corrosion layer. Wherein the anti-corrosion layer can isolate a high-sulfur environment and prevent the substrate from being corroded; the sulfur phobic layer may prevent sulfur products from depositing and passivating the electrode. The catalytic electrode provided by the invention solves the problems of sulfur reaction corrosion and passivation, shows excellent catalytic activity and stability, and can be used for catalyzing sulfur oxidation reaction for a long time. In conclusion, the method has the advantages of mild conditions, simple process, economy and practicability, and has obvious large-scale industrial production potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic electrode technology, and particularly relates to a method for preparing and applying a room-temperature synthetic catalytic electrode. Background Technology

[0002] The oxygen evolution reaction (OER) is a complex four-electron transfer process. It not only possesses a high theoretical thermodynamic potential (1.23 V vs. RHE), but its slow kinetics also necessitate overcoming significant overpotentials in practical applications, resulting in an actual oxidation potential far exceeding the theoretical value. Compared to electrocatalytic oxidation methods targeting alcohols, aldehydes, or biomass molecules, sulfide electrocatalytic oxidation (SOR) offers significant advantages as an alternative to OER. It significantly lowers the thermodynamic reaction energy barrier (lower oxidation potential), and more importantly, it addresses the common issue of high concentrations of [unspecified compounds] in wastewater from industries such as papermaking, leather tanning, and dyeing. ,and Sulfur is a highly corrosive and toxic pollutant. Furthermore, electrochemical methods offer significant advantages in sulfur-containing wastewater treatment due to their rapid response, cost-effectiveness, eco-friendliness, and ease of operation. Therefore, using SOR (sulfur-retaining oxygen) to replace OER (sulfur-containing wastewater treatment) can simultaneously achieve the recovery of high-value elemental sulfur, as well as the harmless treatment and resource recovery of environmental pollutants. This solves the problems of high-energy-consuming OER and sulfur-containing wastewater pollution, achieving both economic and environmental benefits.

[0003] Although replacing the oxygen evolution reaction (OER) with electrocatalytic sulfur oxidation has theoretical advantages, related research remains very limited. The core bottleneck lies in the strong corrosive and poisoning effect of sulfur on traditional metal electrocatalysts, which significantly shortens catalyst lifetime. To alleviate this problem, two main strategies exist: one is to design a protective layer at the atomic / molecular level to isolate the active sites of the transition metal from the sulfur-containing reaction environment to inhibit corrosion; the other focuses on material compatibility, directly using transition metal sulfide catalysts. The latter strategy is not only more direct in preparation but also has greater application potential due to the inherent lattice matching between sulfide electrodes and sulfide electrolytes. The key to the success of this strategy lies in controlling the redox state of sulfur in the catalyst lattice: when the valence state of S in the catalyst is close to the oxidation state of sulfides in solution, it is more conducive to sulfur release (desulfurization), thereby avoiding the accumulation and blockage of toxic sulfur-containing substances at active sites and alleviating catalyst passivation to some extent. Therefore, developing efficient SOR electrodes has significant scientific importance and broad application prospects. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a room temperature synthesis catalytic electrode that is mild, simple, economical and practical, and its application.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0006] The catalytic electrode includes a substrate and an anti-corrosion layer and a sulfur-repellent layer attached thereon in sequence; the substrate is a blank nickel foam substrate, the anti-corrosion layer is formed by impregnating the nickel foam substrate with an iron salt solution, and the sulfur-repellent layer is formed by electrodepositing the precursor with a cobalt salt solution.

[0007] The method for preparing a room temperature synthetic catalytic electrode involves using a blank nickel foam substrate. First, the nickel foam substrate is impregnated with an iron salt solution to obtain a precursor with an anti-corrosion layer. Then, the precursor is electrodeposited with a cobalt salt solution to form a sulfur-repellent layer on the anti-corrosion layer.

[0008] The impregnation treatment is performed as follows:

[0009] (11) Cut the nickel foam into rectangular pieces, and sonicate them in HCl solution, acetone, ethanol and water in sequence, and dry them for later use;

[0010] (12) Prepare a ferric nitrate solution, and then add sodium thiosulfate to obtain a uniform impregnation solution;

[0011] (13) The nickel foam was immersed in the impregnation solution, then rinsed with water and anhydrous ethanol and dried to obtain S-NiFe LDH / NF.

[0012] In step (11): cut the nickel foam into 1*2 cm pieces. 2 The rectangular slices were ultrasonically treated in 3 M HCl solution for 15 minutes, then ultrasonicated in acetone for 15 minutes, and then ultrasonicated in ethanol and deionized water for 15 minutes respectively. Finally, they were dried in a vacuum oven at 50-60°C.

[0013] In step (12): dissolve ferric nitrate in deionized water and sonicate until completely dissolved; then, dissolve sodium thiosulfate in the ferric nitrate solution and sonicate while shaking until completely dissolved.

[0014] In step (13): the nickel foam is immersed in the impregnation solution for 15-30 seconds, and after the nickel foam is removed, it is rinsed several times with deionized water and anhydrous ethanol, and then dried in a vacuum oven at 50-60°C.

[0015] The concentration of ferric nitrate solution is 1–5 mol / L, and the concentration of sodium thiosulfate solution is 0.1–1 mol / L.

[0016] The electrodeposition process is performed as follows:

[0017] (21) Prepare a thiourea solution, and then add cobalt chloride to obtain an electrolyte;

[0018] (22) Sulfides were deposited on the anti-corrosion layer by electrodeposition. After electrodeposition, the conductive substrate was washed and dried to obtain CoS@S-NiFe LDH / NF.

[0019] In step (21): Thiourea is dissolved in deionized water and sonicated until completely dissolved; then, cobalt chloride is dissolved in the thiourea solution and sonicated until completely dissolved.

[0020] In step (22): Pt counter electrode and Ag / AgCl reference electrode are added, and a conductive substrate with an anti-corrosion layer grown on its surface is used as the working electrode. After electrodeposition, the conductive substrate is washed multiple times, rinsed, and then placed in a vacuum oven at 50-60°C to dry overnight.

[0021] The concentration of thiourea solution was 0.1–1 mol / L, and the concentration of cobalt chloride was 1–10 mmol / L; the electrodeposition voltage was -2–1 V, and the scan rate was 1–10 mV s. -1 The number of cycles is 5 to 200.

[0022] Application of the above-mentioned catalytic electrode or the catalytic electrode obtained by the above preparation method in catalytic electrochemical sulfur oxidation reaction.

[0023] To address the current problems in electrocatalytic sulfur oxidation reactions, the inventors have developed a catalytic electrode comprising a substrate and sequentially attached anti-corrosion and sulfur-repellent layers. The substrate is a blank nickel foam substrate. The anti-corrosion layer is formed by impregnating the nickel foam substrate with an iron salt solution, and the sulfur-repellent layer is formed by electrodepositing a precursor with a cobalt salt solution. Based on this, a corresponding preparation method has also been established. Using a blank nickel foam substrate, the substrate is first impregnated with an iron salt solution to obtain a precursor with an anti-corrosion layer, and then the precursor is electrodeposited with a cobalt salt solution to form a sulfur-repellent layer on the anti-corrosion layer.

[0024] Compared with the prior art, the present invention has the following outstanding technical effects:

[0025] The key raw materials used in this invention (such as ferric nitrate, cobalt chloride, sodium thiosulfate, and thiourea) are widely available, readily accessible, and inexpensive. Compared to relying on expensive and rare precious metal precursors, this raw material system can significantly reduce production costs and has obvious potential for large-scale industrial production.

[0026] The operation process of this invention is simple and easy to implement. It only requires dissolving and ultrasonically dispersing the raw materials, followed by impregnation and electroplating using an electrodeposition process, and then washing and drying, among other conventional steps. The professional skills required of the operators are not high. Moreover, the impregnation and electrodeposition conditions are mild, with the reaction temperature at room temperature. Compared to some sulfur corrosion-resistant and passivation-resistant catalytic electrode synthesis processes (high temperature and high pressure or complex steps), this invention consumes less energy and has no special equipment requirements. Ordinary laboratory or industrial production equipment can meet the needs, reducing equipment investment costs and production difficulty, and more importantly, improving the safety factor.

[0027] In the preparation of the catalytic electrode of this invention, the anti-corrosion layer can isolate the high-sulfur environment and prevent the substrate from being corroded; the deposited sulfides can act as a sulfur-repellent layer for desulfurization, preventing the deposition of sulfur products and passivation of the electrode. Studies have shown that this invention, when catalyzing the electrochemical sulfur oxidation reaction (SOR) in a 1.0 M NaOH (containing 1.0 M Na2S) electrolyte, achieves... At high current densities, it can achieve low overpotentials of 300–310 mV, exhibiting excellent catalytic activity and stability; it can efficiently achieve the dual objectives of desulfurization and elemental sulfur recovery. Furthermore, the electrode of this invention possesses good stability, demonstrating high activity retention in multiple electrochemical oxidation tests (after 2000 h of constant voltage testing, its SOR catalytic current density mostly remained at 200 mA cm⁻¹). -2 (Approximately 1000 meters), possessing excellent long-term operational potential.

[0028] In summary, the catalytic electrode of this invention solves the problems of corrosion and passivation in sulfur reactions and can be used for long-term catalytic sulfur oxidation reactions. Attached Figure Description

[0029] Figure 1 These are the X-ray powder diffraction patterns of Example 4 CoS@S-NiFe LDH / NF-80 and Example 1 S-NiFe LDH / NF.

[0030] Figure 2 This is a scanning electron microscope image of CoS@S-NiFe LDH / NF-80 from Example 4.

[0031] Figure 3 This is the elemental distribution diagram of CoS@S-NiFe LDH / NF-80 in Example 4.

[0032] Figure 4 This is a scanning electron microscope cross-sectional image of CoS@S-NiFe LDH / NF-80 in Example 4.

[0033] Figure 5 These are linear scan voltammetry curves for Examples 1 and 3-7.

[0034] Figure 6 This is the linear sweep voltammetry curve of CoS@S-NiFe LDH / NF-80 in Example 4.

[0035] Figure 7 This is the contact angle diagram of CoS@S-NiFe LDH / NF-80 in Example 4.

[0036] Figure 8 This is the stability graph of CoS@S-NiFe LDH / NF-80 in Example 4.

[0037] Figure 9 The images show the X-ray powder diffraction pattern of the product powder after electrolysis of CoS@S-NiFe LDH / NF-80 in Example 4, and a photograph of the collected sulfur powder. Detailed Implementation

[0038] Example 1: Preparation of S-NiFe LDH / NF catalyst

[0039] (11) Cut the nickel foam into 1*2 cm pieces. 2 The rectangular sheet was ultrasonically treated in 3 M HCl solution for 15 minutes, then ultrasonicated in acetone for 15 minutes, and then ultrasonicated in ethanol and deionized water for 15 minutes respectively to remove oil and impurities from the surface of the nickel foam. It was then dried in a vacuum oven at 50-60℃, and the surface showed a silver-gray metallic luster. The ultrasonic frequency was 53Hz and the temperature was room temperature.

[0040] (12) Dissolve ferric nitrate in deionized water and sonicate until completely dissolved; then, dissolve sodium thiosulfate in ferric nitrate solution and sonicate while shaking until completely dissolved to obtain 10 mL of uniform impregnation solution (the concentration of ferric nitrate solution is 3 mol / L and the concentration of sodium thiosulfate is 1 mol / L); wherein, the sonication frequency is 53 Hz and the temperature is room temperature.

[0041] (13) The dried blank nickel foam is immersed in the impregnation solution for 15 seconds (at room temperature). After removing the nickel foam, it is rinsed with deionized water until the water is clear and colorless. Then it is rinsed with anhydrous ethanol and dried in a vacuum oven at 50-60°C to obtain S-NiFe LDH / NF.

[0042] Example 2 Preparation of S-NiFe LDH / NF-1 catalyst

[0043] The preparation method and steps are basically the same as in Example 1, except that in step (13), the dried blank nickel foam is immersed in the impregnation solution for 30 seconds (at room temperature). After drying, it was found that the nickel foam was black. If the immersion time was too long, the nickel foam would turn into powder and its porous structure would collapse, making it unusable as an electrode.

[0044] Analysis of the two examples above shows that the immersion time needs to be strictly controlled. If the immersion time is too long, the nickel foam will be over-immersed, causing the nickel foam structure to collapse and pulverize. Conversely, if the immersion time is too short, the surface of the nickel foam will not be completely blackened and will still show a silvery-gray metallic luster, indicating that the anti-corrosion layer has not completely covered the surface of the nickel foam. Both excessively long and short immersion times will affect the anti-corrosion layer on the nickel foam. Therefore, it is recommended that the immersion time should not exceed 30 seconds.

[0045] Example 3 Preparation of CoS@S-NiFeLDH / NF-40 catalyst

[0046] (21) Dissolve thiourea in deionized water and sonicate until completely dissolved; then, dissolve cobalt chloride in the thiourea solution and sonicate until completely dissolved to obtain 50 mL of electrolyte (the concentration of thiourea solution is 0.75 mol / L and the concentration of cobalt chloride is 5 mmol / L); wherein, the sonication frequency is 53 Hz and the temperature is room temperature;

[0047] (22) A Pt counter electrode and an Ag / AgCl reference electrode were added, and a conductive substrate with an anti-corrosion layer grown on its surface (dried nickel foam from Example 1) was used as the working electrode. Cyclic voltammetry (CV) was used to deposit sulfides on the anti-corrosion layer. After electrodeposition, the conductive substrate was repeatedly washed to remove residual reagents (first rinsed with water several times, then rinsed with anhydrous ethanol). After rinsing, it was placed in a vacuum oven at 50–60°C and dried overnight to obtain CoS@S-NiFeLDH / NF-40 material. The potential window range was -2 to 1 V, and the scan rate was 5 mV s. -1 The number of cycles is 40, and the deposition temperature is room temperature.

[0048] Example 4 Preparation of CoS@S-NiFeLDH / NF-80 catalyst

[0049] The preparation method is basically the same as in Example 3, except that in step (22), the number of cycles is 80, and CoS@S-NiFeLDH / NF-80 material is obtained.

[0050] Example 5 Preparation of CoS@S-NiFeLDH / NF-120 catalyst

[0051] The preparation method is basically the same as in Example 3, except that in step (22), the number of cycles is 120, and CoS@S-NiFeLDH / NF-120 material is obtained.

[0052] Example 6 Preparation of CoS@S-NiFeLDH / NF-160 catalyst

[0053] The preparation method is basically the same as in Example 3, except that in step (22), the number of cycles is 160, and CoS@S-NiFeLDH / NF-160 material is obtained.

[0054] Example 7 Preparation of CoS / NF catalyst

[0055] The preparation method is basically the same as in Example 3, except that in step (22), the number of cycles is 80, and the substrate is a dried blank nickel foam (without impregnation treatment) to obtain CoS / NF material.

[0056] Electrocatalytic performance evaluation

[0057] The electrocatalytic performance of the catalyst was measured using an electrochemical workstation (CHI760E). In the electrocatalytic test, a self-supporting CoS@S-NiFe LDH / NF-80 catalyst electrode, a stone rod electrode, and a mercury / mercury oxide electrode were used as the working electrode, counter electrode, and reference electrode, respectively, forming a standard three-electrode testing system. An electrocatalytic coupling system was formed by using a stone rod electrode as the catalytic cathode (1.0 M NaOH) for the HER half-reaction and CoS@S-NiFe LDH / NF-80 as the catalytic anode (1.0 M NaOH + 1.0 M Na2S) for the SOR half-reaction, separated by a proton exchange membrane.

[0058] The obtained materials were tested and examined accordingly, with the results of Example 4 as follows: Figures 1 to 8 As shown, the details are as follows:

[0059] Figure 1 The X-ray powder diffraction patterns of Example 4 CoS@S-NiFe LDH / NF-80 and Example 1 S-NiFe LDH / NF show the presence of the Ni peak. However, the peaks on the nickel foam substrate are so strong that they mask the other peaks.

[0060] Figure 2 This is a scanning electron microscope image of CoS@S-NiFe LDH / NF-80 from Example 4, showing that the nanosheets are stacked to form nanoflowers.

[0061] Figure 3 The elemental distribution diagram of CoS@S-NiFe LDH / NF-80 in Example 4 confirms the uniform distribution of S, Ni, Fe, and Co in the CoS@S-NiFe LDH / NF-80 nanomaterial.

[0062] Figure 4 This is a SEM cross-sectional image of CoS@S-NiFe LDH / NF-80 in Example 4, which clearly shows a sandwich structure formed by the sulfur-repellent layer, the anti-corrosion layer, and the nickel foam layer.

[0063] Figure 5The figures show the linear sweep voltammetry curves for Examples 1 and 3-7. As can be seen from the figures, the SOR catalytic performance is best with Example 4 CoS@S-NiFe LDH / NF-80, which has 80 deposition layers. As the number of deposition layers increases from 40 to 160, the catalytic performance first increases and then decreases, indicating that more deposition layers are not necessarily better. At 0.3 V vs. RHE, the current density of Example 4 CoS@S-NiFe LDH / NF-80 reaches 100 mA, while Example 7 CoS / NF reaches 54.6 mA, and Example 1 S-NiFe LDH / NF only reaches 16.78 mA. This demonstrates that the catalytic electrodes of Examples 3-6 prepared using both the impregnation and deposition methods are superior to the catalytic electrodes of Examples 1 and 7 prepared using the one-step method.

[0064] Figure 6 This is the linear sweep voltammetry plot of CoS@S-NiFe LDH / NF-80 from Example 4. It can be seen that, compared to the OER reaction, at 100 mA cm⁻¹... -2 At the given current density, the voltage required for SOR is 0.3V, while the voltage required for OER exceeds 1.5V. The potential difference between the two is 1263mV, further confirming that the SOR reaction has a lower thermodynamic potential than the OER reaction. Therefore, using SOR instead of OER can not only lower the anode potential and improve the energy efficiency of the catalytic reaction, but also help reduce energy consumption.

[0065] Figure 7 This is the contact angle diagram of CoS@S-NiFe LDH / NF-80 in Example 4. A contact angle greater than 90 degrees between the sulfur droplet and the catalyst, with a larger angle, is more conducive to desulfurization; conversely, a contact angle less than 90 degrees indicates a stronger affinity for sulfur, which can easily lead to sulfur deposition and catalyst surface passivation. As shown in the diagram, the contact angle is 115 degrees, greater than 90 degrees, indicating that CoS@S-NiFeLDH / NF-80 has the ability to desulfurize in a timely manner, thereby mitigating catalyst passivation by sulfur products.

[0066] Figure 8 This is Example 4, the voltage constant stability test of CoS@S-NiFe LDH / NF-80. The voltage constant test was performed at 0.55 V vs. RHE, with the electrolyte changed at regular time intervals, because product accumulation can affect electrode performance. As shown in the figure, the current density remained mostly at 200 mA cm⁻¹ after prolonged electrolysis. -2 The electrode performance remained good throughout the process, demonstrating excellent durability in sulfur ion recovery.

[0067] Figure 9This is the X-ray powder diffraction pattern of the product powder after electrolysis of CoS@S-NiFe LDH / NF-80 in Example 4. The yellow product obtained by acidifying the anolyte, centrifugation, washing, and drying matches the S8 standard card, and the presence of sulfur is confirmed by the X-ray diffraction pattern.

Claims

1. A catalytic electrode, characterized in that... It includes a substrate and an anti-corrosion layer and a sulfur-repellent layer attached thereon in sequence; the substrate is a blank foamed nickel substrate, the anti-corrosion layer is formed by impregnating the foamed nickel substrate with an iron salt solution, and the sulfur-repellent layer is formed by electrodepositing the precursor with a cobalt salt solution.

2. A method for preparing a room-temperature synthetic catalytic electrode, characterized in that: Using a blank nickel foam substrate, the nickel foam substrate is first impregnated with an iron salt solution to obtain a precursor with an anti-corrosion layer. Then, the precursor is electrodeposited with a cobalt salt solution to form a sulfur-repellent layer on the anti-corrosion layer.

3. The preparation method according to claim 2, characterized in that... The impregnation treatment is performed as follows: (11) Cut the nickel foam into rectangular pieces, and sonicate them in HCl solution, acetone, ethanol and water in sequence, and dry them for later use; (12) Prepare a ferric nitrate solution, and then add sodium thiosulfate to obtain a uniform impregnation solution; (13) The nickel foam was immersed in the impregnation solution, then rinsed with water and anhydrous ethanol and dried to obtain S-NiFeLDH / NF.

4. The preparation method according to claim 3, characterized in that: In step (11): cut the nickel foam into 1*2 cm pieces. 2 The rectangular slices were ultrasonically treated in 3 M HCl solution for 15 minutes, then ultrasonicated in acetone for 15 minutes, and then ultrasonicated in ethanol and deionized water for 15 minutes respectively. Finally, they were dried in a vacuum oven at 50-60°C. In step (12): dissolve ferric nitrate in deionized water and sonicate until completely dissolved; then, dissolve sodium thiosulfate in the ferric nitrate solution and sonicate while shaking until completely dissolved. In step (13): the nickel foam is immersed in the impregnation solution for 15-30 seconds, and after the nickel foam is removed, it is rinsed several times with deionized water and anhydrous ethanol, and then dried in a vacuum oven at 50-60°C.

5. The preparation method according to claim 4, characterized in that: The concentration of the ferric nitrate solution is 1–5 mol / L, and the concentration of the sodium thiosulfate solution is 0.1–1 mol / L.

6. The preparation method according to claim 2, characterized in that... The electrodeposition process is performed as follows: (21) Prepare a thiourea solution, and then add cobalt chloride to obtain an electrolyte; (22) Sulfides were deposited on the anti-corrosion layer by electrodeposition. After electrodeposition, the conductive substrate was washed and dried to obtain CoS@S-NiFe LDH / NF.

7. The preparation method according to claim 6, characterized in that: In step (21): Thiourea is dissolved in deionized water and sonicated until completely dissolved; then, cobalt chloride is dissolved in the thiourea solution and sonicated until completely dissolved. In step (22): Pt counter electrode and Ag / AgCl reference electrode are added, and a conductive substrate with an anti-corrosion layer grown on its surface is used as the working electrode. After electrodeposition, the conductive substrate is washed multiple times, rinsed, and then placed in a vacuum oven at 50-60°C to dry overnight.

8. The preparation method according to claim 7, characterized in that: The concentration of the thiourea solution is 0.1–1 mol / L, and the concentration of cobalt chloride is 1–10 mmol / L; the electrodeposition voltage is -2–1 V, and the scan rate is 1–10 mV s. -1 The number of cycles is 5 to 200.

9. The application of the catalytic electrode of claim 1 or the catalytic electrode obtained by any of the preparation methods of claims 2 to 8 in the catalytic electrochemical sulfur oxidation reaction.

Citation Information

Cited By

  • ZnIn2S4 / NiFeOOH-S film electrode

    CN117604553A

  • zincln2s4 / nifeohh-s thin film electrode

    CN117604553B